1986
DOI: 10.1002/bit.260281205
|View full text |Cite
|
Sign up to set email alerts
|

The application of a novel heat flux calorimeter for studying growth of Escherichia coli W in aerobic batch culture

Abstract: The modification and principle of a novel heat flux calorimeter for the in siru, on-line measurement of the heat generated during microbial growth is described. Data concerning the physical characterization of the calorimeter as a fermentor, including stability and sensitivity of the heat signal, are presented. The calorimeter has been successfully applied to the study of the aerobic batch culture of Escherichia coli W on glucose under carbon and nitrogen limitation. A direct correlation between growth and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…(11). It has been shown that expression (6) reduces to a constant of about 460 kJ/mole of 0, for strongly aerobic processes.I7 In an increasingly fermentative metabolism, Yi,s will fall and Y & will increase in such a way that the denominator, which in fact is an expression for Y&, will become zero and will drive the heat yield to infinity.…”
Section: General Expressions For the Heat Yieldsmentioning
confidence: 97%
See 1 more Smart Citation
“…(11). It has been shown that expression (6) reduces to a constant of about 460 kJ/mole of 0, for strongly aerobic processes.I7 In an increasingly fermentative metabolism, Yi,s will fall and Y & will increase in such a way that the denominator, which in fact is an expression for Y&, will become zero and will drive the heat yield to infinity.…”
Section: General Expressions For the Heat Yieldsmentioning
confidence: 97%
“…In these equations, y, and 6, are the degrees of reductance and hydrogenation, respectively, which are defined as fol- (11) i o~~: '~ y l = 4 + el, -2el, -3e,,…”
Section: Derivation Of a Model For Mixed Respiratory/fermentative Metmentioning
confidence: 99%
“…), the precursors of the secondary metabolites, NAD(P)H, RNA, DNA, proteins, and cell morphology [130,257]. The heat generated by the microorganisms [258][259][260][261][262][263] and the intracellular enzyme activities and metabolites [264][265][266][267][268][269] are monitored as well. In special cases, the intracellular enzyme activities were measured on-line [270][271][272][273][274].…”
Section: Process Identification By Advanced Monitoring and Controlmentioning
confidence: 99%
“…As early as 1968, Cooney et al 24) pioneered the completely novel development of calorimeters at the bench scale. Three different types of bench scale calorimeters for use in biotechnology have been described in the literature to date [24][25][26][27][28][29][30][31]. They all consist of a laboratory bioreactor with a nominal volume comprising between 2 and 14 1, which can be operated much like a standard laboratory reactor, while featuring the necessary equipment for measuring the heat generated by the microbial culture in situ.…”
Section: Introductionmentioning
confidence: 99%
“…It is obvious that this new form of calorimetry, which has become known in chemical engineering literature as 'Isothermal Reaction Calorimetry' 32) is especially well suited for quantitative investigations of microbially generated heat-fluxes under technically realistic processing conditions. Their main disadvantage, a relatively low sensitivity, can, in part, be overcome by using a novel "heat-flux" measuring principle 30) Judging from published results, the more recent experimental techniques developed in the last decade will probably expand the usefulness of calorimetry in biotechnology from the traditional field of utilization of microcalorimetry to incorporate more quantitative process-engineering related applications, some of which are summarized in Table 2.…”
Section: Introductionmentioning
confidence: 99%